A Multi-Pronged Technique for Identifying Equisetum palustre and Equisetum arvense—Combining HPTLC, HPLC-ESI-MS/MS and Optimized DNA Barcoding Techniques - Afoke Ibi; Min Du; Till Beuerle; Dennis Melchert; Julia Solnier; Chuck Chang (Plants, 2022)
The most prominent horsetail species, Equisetum arvense, has an array of different medicinal properties, thus the proper authentication and differentiation of the plant from the more toxic Equisetum palustre is important. This study sought to identify different samples of E. arvense and E. palustre using three analytical methods. The first method involved the use of HPTLC analysis, as proposed by the European Pharmacopoeia. The second, HPLC-ESI-MS/MS, is capable of both identification and quantification and was used to determine the Equisetum alkaloid content in each sample. A third method was DNA barcoding, which identifies the samples based on their genetic make-up. Both HPTLC and HPLC-ESI-MS/MS proved to be suitable methods of identification, with HPLC-ESI-MS/MS proving the more sophisticated method for the quantification of alkaloids in the Equisetum samples and for determining the adulteration of E. arvense. For DNA barcoding, optimal primer pairs were elucidated to allow for the combined use of the rbcL and ITS markers to accurately identify each species. As new DNA marker sequences were added to GenBank, the reference library has been enriched for future work with these horsetail species.